Knowledge of students on providing premedical first aid - Woźniak, Krystyna; Jędrzejczyk-Cwanek, Marzena; Ozga, Dorota; Lewandowski, Bogumił (Journal of Education, Health and Sport, 2017)
Expertise in providing first aid, ensuring an appropriate support until qualified services arrive reduces consequences of injury or getting ill and increases chance for surviving of the injured people at the same time. The aim of the research was to recognise and evaluate level of knowledge among students of University of Rzeszów and State Higher School of Vocational Education in Sanok on providing premedical first aid. A group of 109 students was subject to research. A method of a diagnostic survey was used in the research where a survey questionnaire of authors’ own development was used as a research tool. Results Most of respondents tested, that is 53.2 %, showed lack of a respective preparation to provide first aid. Proper actions to raise the level of knowledge should be undertaken as soon as possible, not only among students but in the whole society, by implementing subject matter of life-saving to curricula starting at the early school education. Conclusions: Knowledge obtained during previous training sessions was too superficial and did not reflect the students’ life-saving skills, knowledge on providing premedical first aid thus did not have influence on actions being undertaken. Obtained results prove necessity to provide training sessions on life-saving activities on a regular basis. The majority of students is interested in deepening their